El desarrollo de la tradición Edesana. Literatura, imagen y poder en la Mesopotamia tardorromana - Francisco, Héctor R. (Byzantion Nea Hellás, 2015)
The Legend of King Abgar and the origins of the Church at Edessa is part of a complex literary tradition which has been developed from the late third century until the early seventh century. In the article, we draw attention to the early stages of this legend through its Greek and Syriac versions. Our aim is to compare the distinct features in the different traditions which allow us to settle the historical context in which they have been written. The central issue of this article is to explain how the different compositions of the same story show two opposite attitudes towards both the Church's hierarchy and ecclesiology in the culture of Late Antiquity (both Greek and Sayriac).